Integrating Network Pharmacology and Experimental Validation to Decipher the Mechanism of Action of Astragalus–Atractylodes Herb Pair in Treating Hepatocellular Carcinoma - Liang Y; Xie Y; Liu X; Yu L; Yan H; Shang Z; Wu Y; Cai X; Shi W; Du J; Yang Z (Dove Medical Press, 2024)
Yuling Liang,1,* Yuqing Xie,1,* Xiaoli Liu,1 Lihua Yu,1 Huiwen Yan,1 Zimeng Shang,1 Yuan Wu,1 Xue Cai,2 Wanxin Shi,2 Juan Du,3 Zhiyun Yang1 1Center of Integrative Medicine, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People's Republic of China; 2Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China; 3Beijing Key Laboratory of Emerging Infectious Diseases, Institute of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People's Republic of China*These authors contributed equally to this workCorrespondence: Juan Du, Beijing Key Laboratory of Emerging Infectious Diseases, Institute of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People's Republic of China, Email duj656@163.com Zhiyun Yang, Center of Integrative Medicine, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People's Republic of China, Tel +86-10-84322148, Email yangzhiyun2016@163.comPurpose: Traditional Chinese medicine (TCM) therapy is an important means to treat hepatocellular carcinoma (HCC), Astragalus (Latin name: Hedysarum Multijugum Maxim; Chinese name: Huangqi, HQ) and Atractylodes (Latin name: Atractylodes Macrocephala Koidz; Chinese name: Baizhu, BZ) (HQBZ), a classic herb pair, is often used in combination to HCC. However, the main components and potential mechanisms of HQBZ therapy in HCC remain unclear. This study aimed to identify the potential active ingredients and molecular mechanisms of action of HQBZ in HCC treatment.Methods: The HQBZ-Compound-Target-HCC network and HQBZ-HCC transcriptional regulatory network were constructed to screen the core active compound components and targets of HQBZ therapy for HCC. Molecular docking techniques are used to verify the stability of binding core active compound components to targets. GO and KEGG enrichment analysis were used to explore the signaling pathway of HQBZ in HCC treatment, the mechanism of HQBZ treatment of HCC was verified based on in vivo H22 tumor bearing mice and in vitro cell experiments.Results: Network pharmacology and molecular docking studies showed that HQBZ treatment of HCC was related to the targeted regulation of IL-6 and STAT3 by the active compound biatractylolide, KEGG pathway enrichment analysis suggest that HQBZ may play a role in the treatment of HCC through IL-6/STAT3 signaling pathway. In vitro experiment results proved that HQBZ could regulate IL-6/STAT3 signaling pathway transduction on CD8+T cells, inhibit CD8+T cell exhaustion and restore the function of exhausted CD8+T cells. In vivo experiment results proved that HQBZ can regulate IL-6/STAT3 signaling pathway transduction in H22 liver cancer model mouse tumor tissue, increased the proportion of tumor infiltrating CD8+T cells.Conclusion: This study found that HQBZ may play a therapeutic role in HCC by targeting IL-6 and STAT3 through biatractylolide, its mechanism of action is related to regulating IL-6/STAT3 signaling pathway, reversing T cell failure and increasing tumor infiltration CD8+T cells.Keywords: Astragalus-Atractylodes herb pair, hepatocellular carcinoma, IL-6/STAT3 signaling pathway, molecular docking, network pharmacology